The Effect Of Financial Literacy And Inclusion Finance On Msme Performance (Case Study On Msmes Medan Districtsandpaper) - Sari, Warsani Purnama; Prayudi, Ahmad; Ramadani, Mawaddah; Pribadi, Teddi (Accounting and Business Journal, 2024)
The study purpose to analyze the influence of financial literacy and financial inclusion on the performance of MSMEs in Medan Amplas District, both partially and simultaneously. The type of research used in this research is quantitative research using an associative approach. The population and sample in this research were 107 MSMEs in Medan Amplas District. The type of data used in this research is quantitative data. The data source used in this research is primary data. The data collection method used in this research is a questionnaire. The data analysis method used is multiple linear regression analysis using the SPSS (Statistical Program For Social Science) technique version 17. The research results show that partially and simultaneously financial literacy and financial inclusion have a positive and significant effect on the performance of MSMEs in Medan Amplas District.